An empirical investigation of pricing and competition in the UK credit card market - Knight, Helen Julie (2010)
The UK credit card market has attracted significant interest since the late 1990s, partly because of the strong growth it has enjoyed and also because of the aggressive behaviour of a number of new entrants. The credit card market consists of two very different businesses: card issuance - the "consumer-end", which provides credit cards and bears the credit risk of the customer and merchant acquiring, and the "backroom business", which recruits outlets to accept credit cards and undertakes the processing of transactions. The two businesses are distinct and in the UK only a small number of firms operate within each segment. This thesis concentrates on issues connect to the card issuance business.